Participation in Professional Centres from the Perspective of Children's/Adolescent's Personal and School/Vocational Life Histories - Mateja Marovič,; Ana Bogdan Zupančič, (Revija za elementarno izobraževanje, 2024)
The paper deals with the field of participatory action of individuals placed in professional centres, which represents a special conceptual challenge in both the theory and practice of such engagement.We present the results of a quantitative study involving 231 children/adolescents from all professional centres (more specifically, residential treatment institutions and housing groups) in Slovenia, which provide education for children/adolescents with emotional and behavioural difficulties and/or disorders.The results show that the participatory involvement of children/adolescents in such institution – especially in support processes that have a significant impact on their personal and school/professional biographies – is not encouraging and that, to a greater extent than in traditional forms of residential treatment institutions, it is in the domain of individuals placed in housing groups.
Keywords: participation of children/adolescents, professional centres, institutional care, personal life history, school/vocational record.; participation of children/adolescents, professional centres, institutional care, personal biography, school/vocational biography.